Endoplasmic Reticulum Calcium Signaling in Hippocampal Neurons - Vyacheslav M. Shkryl (Biomolecules)
The endoplasmic reticulum (ER) is a key organelle in cellular homeostasis, regulating calcium levels and coordinating protein synthesis and folding. In neurons, the ER forms interconnected sheets and tubules that facilitate the propagation of calcium-based signals. Calcium plays a central role in the modulation and regulation of numerous functions in excitable cells. It is a versatile signaling molecule that influences neurotransmitter release, muscle contraction, gene expression, and cell survival. This review focuses on the intricate dynamics of calcium signaling in hippocampal neurons, with particular emphasis on the activation of voltage-gated and ionotropic glutamate receptors in the plasma membrane and ryanodine and inositol 1,4,5-trisphosphate receptors in the ER. These channels and receptors are involved in the generation and transmission of electrical signals and the modulation of calcium concentrations within the neuronal network. By analyzing calcium fluctuations in neurons and the associated calcium handling mechanisms at the ER, mitochondria, endo-lysosome and cytosol, we can gain a deeper understanding of the mechanistic pathways underlying neuronal interactions and information transfer.